2014
DOI: 10.5603/ait.a2017.0047
|View full text |Cite
|
Sign up to set email alerts
|

ET-View compared to direct laryngoscopy in patients with immobilized cervical spine by unexperienced physicians: A randomized crossover manikin trial

Abstract: Background: Immobilization of the cervical spine is indicated in all patients with the potential risk of any cervical spine injury. Airway management in these patients is challenging and direct laryngoscopy is the standard of care. Videolaryngoscopes like the ET-View were introduced into clinical practice to provide better airway visualization and ease intubation. Although the ET-View is essentially a conventional endotracheal tube, it is equipped with a miniature camera in its tip. The ET-View has not been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Thus far, the VST has shown promising results for endotracheal intubation via supraglottic airway devices [ 11 , 17 ], in mannikins [ 18 22 ] and in a cadaver study [ 23 ]. Furthermore, the guidance of percutaneous dilatational tracheostomy by VST has been evaluated and shown to be feasible [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the VST has shown promising results for endotracheal intubation via supraglottic airway devices [ 11 , 17 ], in mannikins [ 18 22 ] and in a cadaver study [ 23 ]. Furthermore, the guidance of percutaneous dilatational tracheostomy by VST has been evaluated and shown to be feasible [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above tendency concerned both the total meta-analysis outcome and subgroup analysis, particularly intubation under normal airway, cervical spine immobilisation with cervical collar, or continuous chest compression scenarios. In the case of the overall success rate of intubation, Karczewska et al demonstrated that intubators were able to intubate patients with a 100% success rate for both VivaSight and direct laryngoscope under cervical spine immobilisation with a vacuum mattress [13]. 100% effectiveness of intubation with the discussed methods was also observed by Gawłowski et al in the cervical spine man-fIGuRe 6.…”
Section: Discussionmentioning
confidence: 79%
“…4). The analysis in subgroups showed that the above trend was observed in each subgroup [13] assessed intubation in cervical spine immobilisation with a vacuum mattress scenario and also showed the advantage of VivaSight over DL (90% vs. 60%; RR = 1.50 [1.17, 1.92]; p = 0.001). In contrast, the Truszewski et al [20] study showed the advantage of…”
Section: Time To Intubationmentioning
confidence: 78%
“…Even though we included novice residents, their failure rate reached only 6.9%. According to the manikin study [17], when they applied cervical collars to the manikins, all of their CL grades were II and III, and the intubation success rate reached 100% with TVT compared to 84% with direct laryngoscopy. These results imply that endotracheal intubation with TVT under assist of direct laryngoscopy provides easier intubation conditions and a higher success rate.…”
Section: Discussionmentioning
confidence: 99%